2019
DOI: 10.1177/0888406419869029
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Delivered Training to Promote Paraprofessional Implementation of Systematic Instruction

Abstract: As paraprofessionals gain more instructional responsibilities for individual students, feasible training strategies must be established to promote effective delivery of instruction. This train-the-trainer study was designed to teach paraprofessionals how to implement an evidence-based instructional practice under the direction of the classroom teacher. After receiving training from a university researcher, a special education teacher trained three paraprofessionals to implement constant time delay whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Paraeducators serve a variety of students and fill a range of roles in the classroom. A systematic approach to paraeducator supervision is needed to ensure high-quality student outcomes (Walker et al, 2019). Indeed, research has shown that even minimal training for paraeducators can improve outcomes for students with special needs (Brock & Carter, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Paraeducators serve a variety of students and fill a range of roles in the classroom. A systematic approach to paraeducator supervision is needed to ensure high-quality student outcomes (Walker et al, 2019). Indeed, research has shown that even minimal training for paraeducators can improve outcomes for students with special needs (Brock & Carter, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Without a doubt, coaching facilitates practical application of new curricula and EBPs and has been responsible for shaping special education teacher behavior (Horn, Gable, et al, 2020;Maheady et al, 2016;Mueller & Brewer, 2013) as well as paraeducator behavior (Rosenberg et al, 2020;Scheeler et al, 2018;V. L. Walker et al, 2020).…”
Section: Challenges To Implementing Evidence-based Practices In Rural Settingsmentioning
confidence: 99%
“…Based on this result, effective results were obtained showing that teachers developed effective application skills and teacher competencies in effective teaching and learning approaches and gained experience in the use of evidence-based practices. Walker, Douglas, and Brewer (2020) in the study titled Training Given by Teachers to Encourage Professional Application of Systematic Teaching, emphasized that evidence-based practices will be much more effective on children with ASD in providing teachers effective teaching with on-the-job teaching.…”
Section: Study On Teachermentioning
confidence: 99%